Retroperitoneal ewing sarcoma among Asian patients: a case report and review of literature / Amir Al-Amin Mustaff ... [et al.] - Mustaff, Amir Al-Amin; Baharuddin, Kamarul Aryffin; Ibrahim, Kamaruddin; Md Yusoff, Bazli (Faculty of Medicine, 2025)
Retroperitoneal Extraosseous Ewing Sarcoma (EES) is a rare malignancy and poses diagnostic and management challenges. We present a case report of a 32-year-old Malay male who experienced persistent abdominal distension with constitutional symptoms. Imaging studies revealed an aggressive retroperitoneal mass with lymphadenopathy and local invasion. The diagnosis of retroperitoneal EES was conf irmed through histopathological examination. The patient' s condition persisted, but he ref used surgical intervention. To address the persistent pain, the patient underwent coeliac plexus block and neurolysis. We also reviewed case reports regarding retroperitoneal EES f or better insight into the management of this rare sarcoma.